Associations Between Parental Occupational Balance, Subjective Health, and Clinical Characteristics of VLBW Infants - Mona Dür; Mona Dür; Mona Dür; Anna Röschel; Christiane Oberleitner-Leeb; Verena Herrmanns; Verena Herrmanns; Elisabeth Pichler-Stachl; Barbara Mattner; Silvia-Desiree Pernter; Martin Wald; Berndt Urlesberger; et al. (Frontiers Media S.A., 2022)
ObjectiveVery low birthweight (VLBW) infants have an increased risk of mortality and frequently suffer from complications, which affects parental occupational balance. Occupational balance is the satisfaction with one's meaningful activities, which include everyday activities that people need to, want to, and are expected to do. In contrast to work-life balance, the construct of occupational balance addresses different activities equally and it applies to all persons, regardless of whether they are working or not. Parental occupational balance might be related to parents' and VLBW infants' health. Therefore, the objective of this study was to investigate associations between parental occupational balance, subjective health, and clinical characteristics of VLBW infants.MethodsA cross-sectional multicenter study was conducted in six Austrian neonatal intensive care units. Occupational balance and subjective health of parents of VLBW infants were assessed with six self-reported questionnaires. The following clinical characteristics of VLBW infants were extracted from medical records: gestational age, birthweight, Apgar scores, Clinical Risk for Babies II Score, and complications of prematurity. Spearman's rank coefficients were calculated.ResultsIn total, 270 parents, 168 (62%) female and their VLBW infants, 120 (44%) female, were included in this study. Parents' mean age was 33.7 (±6.0) years, mean gestational age of VLBW infants was 27 + 3 (±2) weeks. Associations between parental occupational balance, subjective health, and clinical characteristics of VLBW infants were identified (rs = 0.13 - 0.56; p ≤ 0.05), such as the correlation between occupational areas (rs = 0.22, p ≤ 0.01), occupational characteristics (rs = 0.17, p = 0.01), and occupational resilience (rs = 0.18, p ≤ 0.01) with bronchopulmonary dysplasia of VLBW infants.ConclusionOccupational balance is associated with parents' and VLBW infants' health. Interventions to strengthen parental occupational balance might increase parental health and thereby also improve health and developmental outcomes of their VLBW infants.